Prevalence of heart failure in dengue patients with concurrent capillary leakage syndrome, unveiling ‘leakage-failure coexistence’ - Motalib, Mohammad Abdul; Pramanik, Dipok Kumar (International Journal of Research in Medical Sciences, 2025)
Background: Dengue fever, a mosquito-borne viral infection, has been a growing global health concern with significant morbidity and mortality. Among the myriad complications that Dengue can manifest, capillary leakage syndrome has emerged as a particularly severe and challenging aspect of the disease. Aim of the study: The aim of this study was to assess the prevalence of heart failure in dengue patients with concurrent capillary leakage syndrome. Methods: This cross-sectional observational study was conducted in Department of Medicine, Khwaja Yunus Ali Medical Hospital, Sirajgonj, Bangladesh, during the period from July 2022 to June 2024. Out of 400 cases of dengue fever patients, 50 patients diagnosed with dengue fever with heart failure with concurrent capillary leakage syndrome were included in this study. Result: This study of total 400 participants (mean age 35.4±12.6 years) revealed male predominance (64%, p=0.036) and urban residency (76%, p=0.017). The average presentation delay was 6.2 days, with 30% reporting prior dengue (p=0.025). Laboratory findings showed elevated hematocrit (48.5%±5.2%, p=0.012), hypoalbuminemia (1.8±0.4 g/dl, p=0.001), and raised NT-proBNP (1500 pg/ml, p=0.007), indicating CLS and cardiac stress. Echocardiography identified reduced LVEF (28%), myocarditis (22%), and arrhythmias (16%) on ECG. Predictors of heart failure included NT-proBNP (OR 4.2, p=0.002) and hypoalbuminemia (OR 3.5, p=0.004). Heart failure was present in 5%, highlighting the burden of CLS and cardiac dysfunction, necessitating improved diagnostics and multidisciplinary interventions. Conclusion: This study highlights the multifaceted complications of CLS and cardiac involvement in dengue patients.